Unprecedented reorganization of developmental history of traditional medicine: Part II - Wenxian Liu; Jingjing Le; Jingcheng Dong (World Scientific Publishing, 2021)
According to the development of the times and the typical characteristics of medical stages, traditional medicine can be divided into six aspects: legendary traditional medicine, instinctive traditional medicine, witchcraft traditional medicine, empirical traditional medicine, theoretical traditional medicine and integrated traditional medicine. With regard to witchcraft medicine, primitive religion almost became an important source of human knowledge all over the world because the ability of early human beings to understand and transform nature was extremely limited. Medicine has experienced a history of symbiosis with religion, and the blending of medicine and witchcraft is an early feature and necessary stage of Chinese and Western traditional medicines. As for empirical medicine, it is a kind of medicine in the stage of "knowing its nature". Its main feature is that medical knowledge and technology are mainly based on the practical or applicatory experience (the primary stage of cognition), but not on the "knowing its reason" stage. From the perspective of this development stage, it is a medicine between witchcraft medicine and theoretical medicine.